Economic effect of consumption of sugar-containing beverages in Kazakhstan and regulatory initia tives to reduce their consumption - Omirbayeva, B.; Serikbayev, N. (BUKETOV BUSINESS REVIEW, 2024)
Object: The purpose of the study is to assess the potential economic damage from the consumption of sugar containing beverages based on the DALY coefficient, as well as to study regulatory strategies adopted in various coun tries of the world aimed at reducing the consumption of sugar-containing beverages, for the possibility of their applica tion in Kazakhstan. Methods: Methods of systematic, comparative, functional, economic and statistical analysis and synthesis, math ematical methods were used as the methodological basis of the study. Findings: The addition of unnecessary sugars to food is an important global problem, leading to numerous short- and long-term health problems and increasing health-related costs for both individuals and governments. Excessive sug ar consumption leads to adverse health consequences, including obesity, type 2 diabetes, poor oral health, cancer risks, etc. The global burden of increasing morbidity from the consumption of sugar-containing beverages has serious conse quences not only for health care, but also for the economy as a whole. Thus, the amount of lost profit in the develop ment of diseases and continued consumption of energy drinks will amount to 3.2 trillion tenge. Conclusions: This review summarizes the international experience in the field of taxation of sugar-containing beverages and its effectiveness. Internationally, public health experts recommend taxing sugary drinks as a key part of a comprehensive strategy to fight obesity and diet-related chronic diseases.